2007
DOI: 10.1681/asn.2006111299
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Light Chains Generate Hydrogen Peroxide

Abstract: As low molecular weight proteins, restriction from glomerular filtration is minimized, permitting significant amounts of Ig light chains to be endocytosed into the proximal tubule epithelium, particularly in plasma cell dyscrasias. Recent studies have shown that this effect of concentrating light chains within the proximal tubule alters cell function. This study demonstrated that light chains belonged to a class of proteins that are capable of catalyzing the formation of hydrogen peroxide. Sufficient amounts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 40 publications
(36 reference statements)
4
50
0
Order By: Relevance
“…Thus, as nephrons are lost, the remaining nephrons are exposed to increasing concentrations of polyclonal FLC. Recent studies demonstrated that monoclonal FLC promote proximal tubular injury by increasing intracellular oxidative stress with the subsequent production of monocyte chemoattractant protein 1 (28). Further work has shown that FLC induce epithelial-mesangial transition (29) and activate mesangial cells to proliferate and increase production of matrix proteins (30).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as nephrons are lost, the remaining nephrons are exposed to increasing concentrations of polyclonal FLC. Recent studies demonstrated that monoclonal FLC promote proximal tubular injury by increasing intracellular oxidative stress with the subsequent production of monocyte chemoattractant protein 1 (28). Further work has shown that FLC induce epithelial-mesangial transition (29) and activate mesangial cells to proliferate and increase production of matrix proteins (30).…”
Section: Discussionmentioning
confidence: 99%
“…Light chains that are degraded induce proinflammatory cytokines, such as monocyte chemoattractant protein-1 and IL-6 and -8 (32,33). These light chains also seem to catalyze the production of reactive oxygen species, which in turn, results in inflammatory cell infiltration, matrix deposition, and fibrosis, and it may contribute to epithelial-mesenchymal transformation of renal tubular epithelial cells (34). Both the mitogen-activated kinase and NF-kB pathways mediate the proinflammatory cascade (32,33).…”
Section: Mechanisms Of Myeloma and Plasma Cell-associated Kidney Injurymentioning
confidence: 99%
“…Recently, it has been established that monoclonal FLCs, but not polyclonal light chains, may generate intracellular oxidative stress, particularly hydrogen peroxide (53). These molecules promote redox-signaling events that result in production of chemokines and cytokines, but also in apoptosis of the proximal tubular cells (53)(54)(55)(56).…”
Section: Tubular Injury In Multiple Myelomamentioning
confidence: 99%
“…These molecules promote redox-signaling events that result in production of chemokines and cytokines, but also in apoptosis of the proximal tubular cells (53)(54)(55)(56).…”
Section: Tubular Injury In Multiple Myelomamentioning
confidence: 99%